Analysis of the Influence of Community Cultural Factors on the Movement of Dengue Haemorrhagic Fever Mosquitoes in Malang Regency - Febriani, Reny Tri; Nurwijayanti; Jalu, Prastyantoko Kukuh (Journal Of Nursing Practice, 2026)
Background: Dengue Haemorrhagic Fever (DHF) remains a serious threat in tropical regions, including Indonesia, with a significant increase in cases. Purpose: The spread of this disease is influenced by community cultural factors and behaviours related to environmental sanitation. Cultural differences between rural and urban communities affect dengue prevention efforts. Through the measurement of the House Index (HI) and Container Index (CI), the relationship between community behaviour and mosquito density can be determined. Methods: This study analysed the influence of community cultural factors on the movement and breeding behaviour of Aedes aegypti mosquitoes in Malang Regency. Using a quantitative analytical observational design (cross-sectional), the research was conducted in three subdistricts with the highest DHF cases: Dau, Kepanjen, and Singosari. Results: The results showed that family support for DHF prevention was generally positive but not significantly related to mosquito density (p = 0.796). Conversely, community leader support showed a significant effect (p = 0.044), as residents were more obedient to local leaders’ guidance. Community leaders play a crucial role in dengue control, while family involvement needs to be strengthened through education and active participation. Conclusion: Nurses are advised to empower families and collaborate with community leaders in implementing the 3M Plus movement and culturally based education to reduce mosquito density and Dengue Haemorrhagic Fever cases.